2018
DOI: 10.1111/bcpt.12998
|View full text |Cite
|
Sign up to set email alerts
|

Statins do not Increase the Rate of Bleeding Among Warfarin Users

Abstract: Clinical significance of potential interaction between warfarin and statins is unclear. Our objective was to determine whether use of statins as a class or use of simvastatin modulates the rate of bleeding requiring hospitalization among new warfarin users. Using Finnish healthcare databases, we identified a cohort of 101,588 warfarin initiators between 1 January 2009 and 30 June 2012. By the end of 2012, these patients accumulated 92,695 person-years of exposure to warfarin-only and 60,253 years of exposure t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
13
1

Year Published

2019
2019
2021
2021

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(14 citation statements)
references
References 36 publications
0
13
1
Order By: Relevance
“…The clinical significance of the warfarin-statin interaction has been a matter of discrepancy in previous literature [43,44]. A recent nationwide database study found no association between the concomitant use of statins and an increased rate of bleeding in new warfarin users [45]. We suspect that the inconsistency in the literature about the significance of the warfarin-statin interaction as well as the clinical experience of prescribing physicians on the concomitant use may explain the stable use of statins in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…The clinical significance of the warfarin-statin interaction has been a matter of discrepancy in previous literature [43,44]. A recent nationwide database study found no association between the concomitant use of statins and an increased rate of bleeding in new warfarin users [45]. We suspect that the inconsistency in the literature about the significance of the warfarin-statin interaction as well as the clinical experience of prescribing physicians on the concomitant use may explain the stable use of statins in our study.…”
Section: Discussioncontrasting
confidence: 58%
“…Significantly increased bleeding was observed (OR = 1.50; 95% CI 1.29-1.74). Three retrospective cohort studies 66,70,85 and one case-control study 49 compared to warfarin alone with an increased risk of bleeding (OR = 3.55; 95% CI 2.78-4.54). One RCT, 22 one prospective cohort study, 34 and seven retrospective cohort studies 57,[64][65][66]85,90,91 reported on dual antiplatelet therapy (aspirin and clopidogrel or aspirin and ticlopidine).…”
Section: Platelet Aggregation Inhibitors (Antiplatelet Agents)mentioning
confidence: 99%
“…Five studies (n = 1 421 921) reported on statins. 33,40,46,53,70 All five studies reported rates of clinically relevant bleeding, but only one study (n = 6404) on thromboembolic events and all-cause mortality. 33 Three studies (n = 639,14) reported on fibrates.…”
Section: Lipid-modifying Agentsmentioning
confidence: 99%
See 1 more Smart Citation
“…21 However, more recent nationwide studies of warfarin users in the US and Finland demonstrated no association between bleeding and use of any statin. 22,23 A population-based, nested case-control study of 45 991 elderly patients taking dabigatran etexilate reported that use of simvastatin or lovastatin was associated with a higher risk of major hemorrhage than use of other statins. 15 An explanation of this effect, based on in vitro evidence, is that statins which exist as inactive lactones (such as simvastatin and lovastatin) may increase absorption and systemic exposure of dabigatran because these statins are nearly ten-fold more potent inhibitors of intestinal P-gp.…”
Section: Discussionmentioning
confidence: 99%